2011
DOI: 10.1111/j.1399-0039.2010.01599.x
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium between HLA‐G*0104 and HLA‐E*0103 alleles in Tswa Pygmies

Abstract: Nonclassical human leukocyte antigen (HLA)-G and -E loci are separated by approximately 660 kb on the short arm of chromosome 6. Interestingly, some functional and expression characteristics are relatively identical or associated for both molecules. For example, expression of HLA-E on the cell surface has been linked to preferential binding of nonameric leader peptides derived from the signal sequence of HLA-G. It has been suggested that these two molecules act synergistically in modulating susceptibility to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…We expected to find these results as UTR-5 is associated with HLA-G*01:03 and our team previously showed that the frequency of this allele greatly varies according to location, i.e. from 1.6% in southeast France to 9% in Congo-Brazzaville [48]. Based on these findings, we had speculated that UTR-5 frequency would be higher in sub-Saharan populations.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…We expected to find these results as UTR-5 is associated with HLA-G*01:03 and our team previously showed that the frequency of this allele greatly varies according to location, i.e. from 1.6% in southeast France to 9% in Congo-Brazzaville [48]. Based on these findings, we had speculated that UTR-5 frequency would be higher in sub-Saharan populations.…”
Section: Discussionmentioning
confidence: 65%
“…We showed in a previous study that there is not significant LD between HLA-G and HLA-E in Southeastern French and Teke Congolese, while two haplotypes in Tswa Pygmies, i.e. HLA-G*01:04∼E*01:03:01 and G*01:04∼E*01:01, exhibited highly significant positive and negative LD values respectively [48].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Few data exist concerning the associations between HLA class Ib alleles; all located within a region of 724 kb on chromosome 6 ( Table 1 ) [ 50 52 ]. So far, the studies on HLA-E reported no LD with other HLA class Ib loci [ 35 ], except with HLA-G in isolated populations [ 53 ]. However, some HLA-E and HLA-A alleles have been described as being fully associated, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…See materials and Methods section for specific subjects origin, since not all of them come from Andean area. Brazilians [41], Uros [44], Mayans [44], North Indians [57], Iranians [58], Iraqi [59], Danish [48], Spanish [23], Germans [60], French [61], Polish [62], Han Chinese [63], Koreans [46], Ghanaian [64], African American [64], Pygmies [61], Shona [47].…”
Section: Hla-g*01:05n In Amerindians: Comparison With Worldwide Populmentioning
confidence: 99%